Efeito da intensidade de pastejo na estrutura da comunidade de aranhas do solo - Freiberg, Joice Aline (2017)
Soil fauna assumes a strategic role as a bioindicator of the level of intensification that can be put to agroecosystem. Soil spiders can help understanding the effects of farming practices on systems that seek to combine the land use intensification with sustainability. This study aimed to know the structure of soil spider community in Integrated Crop-Livestock System (ICLS), constituted by soybean-pasture succession and submitted to different grazing intensities. The study was conducted in ICLS, São Miguel das Missões/RS, which since its establishment in 2001 is cultivated with the succession of black oats (Avena strigosa Schreb.) and Italian ryegrass (Lolium multiflorum Lam.) for continuous grazing of cattle in the winter and soybean [Glycine max (L.) Merrill] for grains production in the summer. The experiment comprises a total area approximately 23 hectares, divided into 14 plots that range from 0.8 to 3.6 hectares, according to the treatments applied. The treatments are based on four sward height management: 10, 20, 30 and 40 cm and areas without grazing (SP) as controls. The spiders were sampled with pitfall traps in two years and in two seasons: immediately after the exit of cattle from pasture, in November 2014 and 2015; and immediately after the soybean harvest in May 2015 and 2016. Total abundance, abundance of juveniles, males and females, and richness of species, families and guilds were evaluated. The effects of sward height on abundance and richness were examined through covariance analysis by linear regression models. The composition of the spider community was evaluated through presence and absence patterns of species, families and guilds according to the environmental gradient using the 'Poncho' function. Variance analyzes were performed to families, species and guilds composition, after grazing and after soybean, through the multivariate analysis of variance using Bray-Curtis distance matrices ('adonis'). A total of 3,055 spiders were collected, classified into 23 families and 45 species. Families, species, and guilds composition differed significantly between pasture and soybean. Linyphiidae and Theridiidae were more abundant after pasture, while Theridiidae and Lycosidae were more abundant after soybean. Ostearius melanopygius (O. Pickard- Cambridge, 1880) and Mermessus sp. were more frequent after pasture, while Styposis selis Levi, 1964 and Metaltella simoni (Keyserling, 1878) were more frequent after soybean. A larger number of sheet web builders were found after pasture, in contrast to the ground runners after the soybean harvest. Linear models suggest that the abundance and richness of soil spiders is strongly influenced by sward height management, especially after pasture. However, after the soybean harvest, the vegetal residues added to the soil by the winter pasture, still exert influence and determine, with smaller values, the variation in spider abundance. The reduction in intensification of grazing management benefits the abundance and richness of spiders in Integrated Crop-Livestock System.